Perencanaan implementasi pembelajaran berdiferensiasi dalam pelajaran IPAS pada peserta didik kelas V sekolah dasar - Delia Ayu Windansari; Sri Marmoah Marmoah; Tri Budiarto Budiarto (Universitas Sebelas Maret, 2024)
The aim of research is to describe planning of the implementation differentiated learning in natural and social sciences in class V of the elementary school. The research uses a qualitative approach with a case study. Data collection use observation, interviews, and documentation. The result of research are that differentiated learning planning is carried out by mapping students learning needs based on learning styles through cognitive diagnostic test assessments, noncognitive diagnostic test assessments, and observation. The results of diagnostic assessment show that the percentage of stundent with a visual learning style 53,33%, auditory 13,33%, and kinesthetic 33,33%. Cognitive diagnostic test results to form study groups using the peer tutoring method. The teacher implement continuous observations to determine students’ learning styles. Differentiated learning planning is also implement by creating teaching modules containing learning purpose, learning prosedure, learning media, learning material about human breathing, formatif assessment, and summative assessment. The implications of this research are in accordance with cognitive learning theory which takes into account student differences so that the result of mapping learning needs are used as a designing learning that accommodates learning styles.